Fermentation and rumen kinetics in buffaloes fed hay of Bermuda grass (Cynodon dactylon (L.) Pears) and concentrate with integral or extruded soybean - Delgado, Denia; Franzolin, R.; Mazza, P. H. (Cuban Journal of Agricultural Science, 2011)
Four buffaloes (Bubalus bubalis) of the Mediterranean breed, with average ages of 13 months and initial liveweight of 300 ? 12 kg were used to determine the fermentative characteristics and the rumen kinetics in buffaloes fed hay of Bermuda grass(Cynodon dactylon (L.) Pears) (70 %) and concentrate (30 %), formulated with ground corn and meal of integral crude (CS) or extruded soybean (ES). The pH was inferior (P < 0.01) when using extruded soybean (6. 55) compared with the crude (6. 79). There were not differences between treatments, for the concentration of ammonia nitrogen in the rumen. The average values were of 16.5 and 18.0 mg.dL-1 for the treatments with CS and ES, respectively. The rates of liquid turnover in the rumen were affected (P < 0.05) by the type of diet, with means of 6.17 % h-1 for CS and 7.85 % h-1 for ES. The rumen volume represented 13.3 - 14.6 % of the liveweight of the buffaloes, but it did not differ between treatments. The sampling time did not affect the pH or the total concentrations of short chain fatty acids (SCFA), acetic and butyric acid, but the propionic acid was increasing (P < 0.05) after the morning feeding. The results showed that, in the experimental conditions established, the use of extruded soybean in the concentrate, in respect to the crude soybean, did not affect significantly the fermentation or the rumen volume. Nevertheless, it increased the rate of liquid turnover. The values of pH were kept high and stable and the ammonia concentration was adequate for the rumen microorganisms. Key words: Bubalus bubalis, rumen turnover, pH, volume, supplementation.